Comparison of arterial and venous pH, bicarbonate, Pco2 and Po2 in initial emergency department assessment. Issue 8 (25th July 2007) - Malatesha, G; Singh, Nishith K; Bharija, Ankur; Rehani, Bhavya; Goel, Ashish
Abstract : Objective: To determine the agreement between arterial and venous samples in a pathologically diverse patient population presenting at an emergency department (ED) with a view to obviating the need for arterial blood gas (ABG) analysis in initial ED evaluation. Methods: Prospective study of 95 patients (69 males, 26 females, mean (SD) age 52 (1.6) years) with diverse medical conditions, presenting at a tertiary health centre ED and deemed by the treating physician to require an ABG analysis. Arterial and venous samples for gas analysis were taken as close in time to each other as possible. The data thus obtained were analysed for agreement between pH, Pco 2, Po 2 and bicarbonate using the Bland–Altman method. Results: The arterial and venous values of pH, bicarbonate and Pco 2 show acceptably narrow 95% limits of agreement using the Bland–Altman method (0.13 to −0.1, 4.3 to −5.8 and 6.8 to −7.6, respectively). Agreement in Po 2 measurements was poor (95% limits of agreement 145.3 to −32.9). Conclusion: Venous blood gas analysis for pH, bicarbonate and Pco 2 may be a reliable substitute for ABG analysis in the initial evaluation of an adult patient population presenting to the ED.